Lime mortars with rice husk ash for ancient masonry - Almeida, Nuno G. (2014)
HMC08 - 1st Historical Mortars Conference: Characterization, Diagnosis, Conservation, Repair and Compatibility, LNEC, Lisbon, 24-26 September 2008